Complete chloroplast genome sequence of a novel Withania somnifera (L.) Dunal: Comparative genomics and phylogenetic insights (Bangladesh Journal of Plant Taxonomy, 2024)
This study introduces a novel variety of the highly esteemed medicinal plant Withania somnifera (L.) Dunal from the family Solanaceae. The new variety, Withania somnifera var. abhaica Nadia, A. Ali & M.S. Alwahibi, var. nov., is distributed at high altitudes in the Abha hills of Saudi Arabia. The distinct characteristics of the novel variety of W. somnifera include elliptic-elongated leaves that are thick and semi-succulent in nature, and a fruiting calyx with a bifurcated tip measuring approximately 0.5 mm in length, with each bifurcated tip being botuliform in shape. Using next-generation sequencing (NGS) techniques, we investigated the chloroplast genome of this variety. The complete chloroplast genome of W. somnifera var. abhaica from the Abha region, Saudi Arabia, spans 153,621 bp, with a GC content of 37.7%. It includes a large single-copy (LSC) region of 84,972 bp (GC 35.8%), a small single-copy (SSC) region of 18,400 bp (GC 31.7%), and two inverted repeats (IRs) of 50,249 bp (GC 43.2%). Annotation of the chloroplast genome identified 131 genes, comprising 86 protein-encoding genes (PCGs), eight ribosomal RNA genes, and 37 transfer RNA genes. Repeat analysis identified 38 simple sequence repeats (SSRs) and 50 longer repeat sequences in the plastome. A total of 66 RNA-editing sites were detected across 24 PCGs of the plastome. Comparative genomic studies including synteny analysis, supported and validated the assembled plastome. Nucleotide diversity analysis revealed psbJ, psbA, ndhF, and ycf1 as the most hypervariable barcodes. Phylogenetic analyses suggested the monophyly of the genus Withania. Moreover, the newly sequenced chloroplast genome of W. somnifera var. abhaica was found to be distinct from the typical W. somnifera.Bangladesh J. Plant Taxon. 31(2): 205-223, 2024 (December)